Do Greenhouse Gas Emissions Affect Financial Performance? – an Empirical Examination of Australian Public Firms. (24th September 2013) - Wang, Lei; Li, Steven; Gao, Simon
ABSTRACT Previous studies that have attempted to relate corporate environmental performance to financial performance have generated conflicting results. This paper presents the findings of a study on the relationship between greenhouse gas (GHG) emissions and the financial performance of Australian corporations. Using multiple regression models and data from a sample of 69 Australian public companies, this paper finds a positive correlation between GHG emissions and corporate financial performance. By testing the statistical significance of GHG emission factors in determining company Tobin's q, this study finds that a stronger Tobin's q often correlates with higher GHG emissions across all industry sectors. This finding is contrary to evidence found in previous studies conducted in other countries. The positive correlation found in this study could be explained with reference to the unique economic structure and development of Australia, particularly its dominant mining industry. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment